2019
DOI: 10.20883/jofa.7
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic medicine cabinets — economic aspect activities

Abstract: On the global scale, the market of aesthetic medicine increased in the years 2015–2016 by 8.2% on average, while in Poland by 12–15%. The reasons for the strong development of the Polish market may be related to a systematic increase in the number of affluent Poles [3], ease of access to aesthetic medicine treatments, a change in the way of thinking about this type of treatment, and increased awareness of the appearance and striving to preserve a young and beautiful look. The share of new patients in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In comparison with other studies, the average client's age varies from 41.87 to 47.8 years old. 3,5,6 There are not many epidemiological studies focusing on aesthetic medicine patients in Poland that can be found in the literature. One research stated that the average age of a Polish client is 38 years old, which is in compliance with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison with other studies, the average client's age varies from 41.87 to 47.8 years old. 3,5,6 There are not many epidemiological studies focusing on aesthetic medicine patients in Poland that can be found in the literature. One research stated that the average age of a Polish client is 38 years old, which is in compliance with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Other studies, indicated that the most common types of cosmetic procedures were botulinum toxin, fillers, peels, and mesotherapy, which is also in accordance with our research. 3,4,15 Bearing in mind that 77.88% of respondents feel the increase in their self-esteem after the aesthetic intervention, which was mostly maintained for longer than a month, it can be concluded that aesthetic treatments not only affect the external appearance, but also the psychological well-being. Moreover, these interventions make patients feel more confident (68.34%) and improve not only relationships with other people (13.56%) but also the quality of their sex life (10.54%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations